Hubungan Faktor-Faktor Yang Mempengaruhi Kelancaran Asi Pada Ibu Menyusui Bayi Usia 0-6 Bulan Di Wilayah Kerja Puskesmas Kuta Baro Aceh Besar - Khaira Rizki; Nuriza Nuriza; Nurul Sakdah; Irma Andriani; Mansuriza Mansuriza (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Mother's milk (ASI) is rich in nutrients and is the key to baby's health. Breast milk is the best food that babies aged 0-6 months need for optimal growth and development, increasing body resistance, protecting against infection, forming a healthy digestive system and increasing intelligence. Objective: to determine the relationship between factors that influence the smooth flow of breastfeeding in breastfeeding mothers in the work area of ??the Kuta Baro Aceh Besar Community Health Center. Method: This research is quantitative with an analytical design using a cross-sectional study method. Data were collected using a questionnaire conducted from March 8 to April 4 2023. The population in this study were all breastfeeding mothers who had babies aged 0-6 months, totaling 139 people, using a sampling technique, namely proportional random sampling, of 58 people. Results: Data analysis using chi square with the results of the study shows that there is a relationship between family support and smooth breastfeeding with a value of p= 0.011, there is a relationship between breast care and smooth breastfeeding with a value of p= 0.012, there is a relationship between the frequency of breastfeeding and smooth breastfeeding with a value of p= 0.025 and There is no relationship between the use of contraceptives and the smoothness of breastfeeding with a p value = 0.372. Conclusion: This research is a factor that influences the smoothness of breast milk.